Penerapan Branding Development dalam Acara Car Free Day untuk Penerapan Strategi Komunikasi dan Visual di Perumahan Telaga Harmony Residence - Mulyono, Wahyudi Ahmadi; Agung Rohaji Mulyono; Eti Karningsih; Febri Ramdhani; Lucky Sumardi; Yayan Suryani; Fikri Khaikal Zain; Sunggu Simbolon; Juni Indra Purwanto; Christoper Saputra Gultom; Fitria Bellina; Hernoko Jati Putro (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
This community service research was conducted to examine the implementation of branding development through a Car Free Day event as a strategy to enhance communication and visual identity at Telaga Harmony Residence. The background of this study is the need for effective community branding to strengthen public awareness, social engagement, and residential image in a growing housing area. The objective of this activity was to apply integrated communication and visual strategies that support brand identity through participatory public events. The method employed was a participatory and collaborative approach involving residents, organizers, and local stakeholders, supported by promotional media, visual design elements, and social interaction activities. The findings indicate that the Car Free Day event successfully increased community participation, strengthened visual recognition of the residential brand, and improved public perception of Telaga Harmony Residence as a healthy and environmentally friendly housing area. The implications of this study suggest that community-based events combined with consistent branding and visual communication strategies can effectively enhance residential identity and social cohesion, and may serve as a reference for similar community development programs in the future.